Gamma-irradiation increased meiotic crossovers in mouse spermatocytes - Cai, Xin; Li, Jianhua; Yang, Qingling; Shi, Qinghua (Mutagenesis, 2011)
In mice, the occurrence of immunofluorescent foci for mismatch repair protein MLH1 correlates closely with the occurrence of crossovers, as detected genetically, and MLH1 foci represent virtually all prospective crossover positions. To examine the effects of γ-irradiation on meiotic crossovers in mouse spermatocytes, male mice were subjected to whole-body γ-irradiation at different sub-stages of meiotic prophase and crossovers on synaptonemal complexes (SCs) were analysed by visualising and quantifying the immunofluorescent MLH1 foci. At both 24 and 48 h after exposure, significant dose-dependent increases in the number of total MLH1 foci per spermatocyte were observed at late zygotene-early pachytene with the gradient increase of radiation dose from 0, 1.5, 3-6 Gy. Furthermore, irradiation at preleptotene-leptotene still led to significant dose-dependent increased meiotic crossovers in the spermatocytes analysed 120 h after exposure. In further analysis, these dose-dependent increases in the number of total MLH1 foci per cell were attributed to significant dose-dependent decreases in autosomal SCs with 0 MLH1 focus, and the dose-dependent increases in autosomal SCs with 2 MLH1 foci and the percentage of cells with MLH1 focus on XY bivalent. The increased number of cells with an MLH1 focus on the pseudoautosomal regions (PARs) may indicate that there is a delay in meiotic progression in the irradiated cells. Although significant dose-dependent increases in the number of total MLH1 foci per cell were examined 24, 48 or 120 h after exposure with the gradient increase of radiation doses, these increases were mild compared to the control groups. This suggests that there is tight control of crossover formation (at least with respect to MLH1 foci number). The mechanisms underlying irradiation-induced DNA lesion repair, cellular responses independent of DNA damage and meiotic crossover homeostasis in mammals will be the subjects of future study.